Combined chemo- and immunotherapy of tumors induced in mice by bcr-abl-transformed cells - Sobotková, Eva; Dušková, Martina; Tachezy, Ruth; Petráčková, Martina; Vonka, Vladimír (Oncology reports, 2009)
For our experiments we selected two oncogenic, bcr-abl-transformed mouse cell lines, viz. B210 and 12B1. Both cell types are capable of inducing leukemia-like disease in syngeneic BALB/c mice after intravenous inoculation. 12B1 cells can moreover form solid tumors after subcutaneous injection. Since immunotherapy would expectedly be most effective in animals in which the tumor mass had been reduced by other therapeutic means, we attempted to develop a combined therapeutic system for suppressing tumor growth. In the present study, mice inoculated with the aggressive 12B1 cells were treated with imatinib mesylate (IM), mouse interferon alpha (IFNalpha) and cyclophosphamide (Cy) in combination with genetically modified tumor cells engineered to produce various cytokines. These cell vaccines had been derived from B210 cells. Therapy with IM or IFNalpha alone or cell immunotherapy alone resulted in partial suppression of tumor growth. Of the different therapeutic regimens tested, a combination of repeated doses of IM, IFNalpha and cell vaccines with one relatively high dose of Cy (200 mg/kg) was the most effective, resulting in tumor-free survival of a large portion of mice. The spleens, livers and bone marrows of the successfully treated animals were tested for the presence of bcr-abl-positive cells by means of RT-PCR technique. Results were negative, this suggesting that the animals had been cleared of residual disease.
Keywords: Granulocyte-Macrophage Colony-Stimulating Factor; Cyclophosphamide; Cancer Vaccines; cyklofosfamid; experimentální nádory; Polymerase Chain Reaction; Mice, Inbred BALB C; interleukin-2; Antineoplastic Agents; Mice; myši inbrední BALB C; zvířata; Piperazines; interleukin-12; Combined Modality Therapy; bcr-abl fúzní proteiny; Pyrimidines; Financing, Organized; protinádorové látky; piperaziny; financování organizované; Interleukin-12; pyrimidiny; protinádorové vakcíny; polymerázová řetězová reakce; kombinovaná terapie; imunoterapie; myši; Fusion Proteins, bcr-abl; ženské pohlaví; Interferon-gamma; transformované buněčné linie; faktor stimulující granulocyto-makrofágové kolonie; Animals; Interleukin-2; interferon gama; Neoplasms, Experimental; Cell Line, Transformed; Immunotherapy; Female